Resource availability and barriers to delivering quality care for newborns in hospitals in the southern region of Malawi: A multisite observational study - Mtisunge Joshua Gondwe; Nicola Desmond; Mamuda Aminu; Stephen Allen (Public Library of Science (PLoS), 2022)
Facility-based births have increased in low and middle-income countries, but babies still die due to poor care. Improving care leads to better newborn outcomes. However, data are lacking on how well facilities are prepared to support. We assessed the availability of human and material resources and barriers to delivering quality care for newborns and barriers to delivering quality care for newborns. We adapted the WHO Service Availability and Readiness Assessment tool to evaluate the resources for delivery and newborn care and barriers to delivering care, in a survey of seven hospitals in southern Malawi between January and February 2020. Data entered into a Microsoft Access database was exported to IBM SPSS 26 and Microsoft Excel for analysis. All hospitals had nursery wards with at least one staff available 24 hours, a clinical officer trained in paediatrics, at least one ambulance, intravenous cannulae, foetal scopes, weighing scales, aminophylline tablets and some basic laboratory tests. However, resources lacking some or all of the time included anticonvulsants, antibiotics, vitamin K, 50% dextrose, oxytocin, basic supplies such as cord clamps and nasal gastric tubes, laboratory tests such as bilirubin and blood culture and newborn clinical management guidelines. Staff reported that the main barriers to providing high-quality care were erratic supplies of power and water, inadequacies in the number of beds/cots, ambulances, drugs and supplies, essential laboratory tests, absence of newborn clinical protocols, and inadequate staff, including paediatric specialists, in-service training, and support from the management team. In hospitals in Malawi, quality care for deliveries and newborns was compromised by inadequacies in many human and material resources. Addressing these deficiencies would be expected to lead to better newborn outcomes.